Computational quantum chemistry - Prasad, Ram Yatan; Pranita (Boca Raton : CRC Press, 2021)
"Computational Quantum Chemistry is an extremely useful tool for teaching and research alike. It stipulates information in an accessible manner for scientific investigators, researchers and entrepreneurs. The book supplies an overview of the field and explains the fundamental underlying principles. It also gives the knowledge of numerous comparisons of different methods. The book consists of a wider range of applications in each chapter. It also provides a number of references which will be useful for academic and industrial researchers. It includes a large number of worked out examples and unsolved problems for enhancing the computational skill of the users. Features: Includes comprehensive coverage of most essential basic concepts. Achieves greater clarity with improved planning of topics and is Readers friendly. Deals with the mathematical techniques which will help the readers more efficient in solving problems. Explains a structured approach for mathematical derivations. A reference book for academicians and Scientific investigators"--
OCLC-licensed vendor bibliographic record.
Keywords: Quantum chemistry -- Data processing; Quantum chemistry -- Mathematics -- Data processing; SCIENCE / Quantum Theory; SCIENCE / Chemistry / Physical & Theoretical; SCIENCE / Chemistry / Industrial & Technical